Pengaruh E-Samsat, Sosialisasi,Dan Kemauan Membayar Pajak Terhadap Kepatuhan Wajib Pajak (Studi Pada Kantor Bersama Samsat Singaraja) - Ketut Oyen Dedy Kurniadi; I Gusti Ayu Ketut Rencana Sari Dewi (Universitas Pendidikan Ganesha, 2021)
This study aims to see the effect of e-Samsat, socialization, and willingness to pay taxes on taxpayers. This study uses quantitative methods, where the data uses a questionnaire instrument. This research was conducted at a government agency, namely the Joint Office of SAMSAT Singaraja. This study uses one type of probability sampling, namely simple random sampling. The sample in this study were motor vehicle taxpayers with a minimum number of respondents 348 people. The data analysis technique used multiple regression analysis with the help of the SPSS program. The results showed that partially e-Samsat, socialization, and willingness to pay taxes had a positive and significant effect on taxpayers.